Shareholders’ rights and corporate meetings post COVID‐19 - CHEN, Christopher Chao-hung (Institutional Knowledge at Singapore Management University, 2020)
This short paper reflects on corporate governance and shareholders’ rights during and following the COVID-19 pandemic. The lockdown has affected the way companies’ organs operate. It is unfortunate that the pandemic took place around the critical time of year when most companies hold annual shareholders’ meetings (or general meetings). How, then, can shareholders exercise their rights? How can the board of directors and senior management function during the lockdown period? Technology naturally provides a solution, similar to online teaching and working from home. However, do virtual and remote meetings serve the purpose of having those meetings? Even when we get over the pandemic, what will the ‘new normal’ be in the future for corporate meetings? This paper seeks to explore some of these issues by using some examples from the Asian market. In the remainder of the paper, we first illustrate the traditional model of corporate decision-making by way of board and general meetings. We consider the costs of holding physical meetings and their benefits. We then briefly examine the feasibility of using electronic meetings on a normal day, and how the pandemic may shape the future use of electronic corporate meetings. We then offer some reflections for policymakers to consider.